2007
DOI: 10.1093/jn/137.3.554
|View full text |Cite
|
Sign up to set email alerts
|

Several Transcription Factors Are Recruited to the Glucose-6-Phosphatase Gene Promoter in Response to Palmitate in Rat Hepatocytes and H4IIE Cells

Abstract: Fatty acids and glucose are strong modulators of the expression of glucose-6-phosphatase (Glc-6-Pase), an enzyme that plays a key role in glucose homeostasis. PUFA inhibit, whereas SFA and monounsaturated fatty acids induce the expression of the Glc-6-Pase gene. Palmitate and oleate are the most abundant fatty acid species in circulation during food deprivation in mammals. Although dietary fats have been shown to modulate the expression of genes involved in both lipid and carbohydrate metabolism in liver, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…1A). Oleate was used as a positive control for nutrient-induced G6pc expression (26). As expected, 20 mM glycerol administration (for 2 h) significantly increased endogenous G6pc expression 1.44 fold (compared with vehicle moter region (−143/+72).…”
Section: Effects Of Glycerol And/or Oleate On G6pc Expression In Fao supporting
confidence: 61%
See 2 more Smart Citations
“…1A). Oleate was used as a positive control for nutrient-induced G6pc expression (26). As expected, 20 mM glycerol administration (for 2 h) significantly increased endogenous G6pc expression 1.44 fold (compared with vehicle moter region (−143/+72).…”
Section: Effects Of Glycerol And/or Oleate On G6pc Expression In Fao supporting
confidence: 61%
“…Using several deletion-or chimeric-constructs of the G6pc promoter, we found that the DNA response element for HNF4α (−77/−65) is critical in the transactivation by glycerol. Administration of a saturated long-chain fatty acid, palmitate, has been shown to increase G6pc transcription by inducing the recruitment of HNF4α to the promoter (26). That study also found that oleate increases G6pc transcription.…”
Section: Temporal Changes Of G6pc Expression By Glycerol And/or Oleatementioning
confidence: 68%
See 1 more Smart Citation
“…In the liver, HNF4α is believed to be involved in protein kinase A regulation of the G6Pase gene (5,23), and its down-regulation is expected to cause the decrease in G6Pase expression. Although the difference was without a statistical significance, the present result of Q-PCR showed that the gene expression of HNF4α tended to be reduced in the green tea group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HNF4α gene expression was also down-regulated by GTB, suggesting an association with the down-regulated gene expression of gluconeogenic enzymes. HNF4α is believed to be involved in protein kinase A's regulation of the G6Pase gene (6,19) and has a key role in regulating the PEPCK gene (9,14). Therefore, its down-regulation is expected to cause a decrease in G6Pase and PEPCK expression.…”
Section: Effects Of Fractions Derived From Gtb On Gene Expression In mentioning
confidence: 99%